2010
DOI: 10.4314/ajtcam.v7i1.57256
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the antioxidant properties of Tualang honey of Malaysia

Abstract: Honey has been used since ancient times for its nutritional as well as curative properties. Tualang honey is collected from wild honey bees' hives on Tualang trees found in the Malaysian rain forest. It has been used traditionally for the treatment of various diseases, where its therapeutic value has partly been related to its antioxidant properties. This study therefore assessed the colour intensity, total phenolic content, antioxidant activity and antiradical activity of gamma irradiated Tualang Honey. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
90
5
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 14 publications
5
90
5
4
Order By: Relevance
“…Studies have indicated the range of health benefits of honey, which includes anti-inflammatory, antioxidant and wound healing activities (Kassim et al, 2010;Mohamed et al, 2010;Al-Waili et al, 2011;Hussein et al, 2012). Honey was also known to exert anti-cancer effects in several types of cancer cells including colon cancer Fukuda et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have indicated the range of health benefits of honey, which includes anti-inflammatory, antioxidant and wound healing activities (Kassim et al, 2010;Mohamed et al, 2010;Al-Waili et al, 2011;Hussein et al, 2012). Honey was also known to exert anti-cancer effects in several types of cancer cells including colon cancer Fukuda et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Honey was also known to exert anti-cancer effects in several types of cancer cells including colon cancer Fukuda et al, 2011). Malaysian local honey especially Tualang honey has been found to induce anti-proliferative effects on cervical and breast cancer cell lines (Mohamed et al, 2010) as well as anti-bacterial activity against Acinetobacter baumanni (Fauzi et al, 2011). Likewise, another local honey, Gelam honey has been shown to inhibit the growth of colon cancer cell line namely HT 29 (Wen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Honey is a natural product of honey bees formed from nectar collected from blossoms and has antioxidant properties (Beretta et al, 2005, Perez et al, 2006, Mohamed et al, 2010. Phenolic compounds have been suggested to be the main antioxidant compounds in the honey as highly significant correlations are found between total phenolic contents and antioxidant and antiradical activities of honey (Beretta et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…One of the proposed therapeutic values is attributed partly due to its antioxidant properties. A study by Mohamedet al [25] showed that TH contains phenolic compounds with strong antioxidant activities. However, to date, the protective effects of honey on PQ toxicity have not been investigated.…”
mentioning
confidence: 99%
“…The same batches of honey were used throughout the analysis. The chemical characteristics including the antioxidant properties of the investigated honey have been previously described [25].…”
mentioning
confidence: 99%